Gambaran Kadar Trigliserida Pada Perokok Aktif Direntang Umur 30-40 Tahun - Darni Yulianti; Salnus, Subakir; Asnidar (Jurnal TLM Blood Smear, 2023)
Background: cigarettes contain nicotine that can harm the body and increase lipolysis which affects the fat profile, one of them is triglycerides. Triglycerides are the most efficient form of fat for storing calories in the process of energy formation in the body. Age is one of the natural factors that usually affects increased levels of triglycerides in the blood so it affects a person’shealth condition. Triglyceride levels in the body <150 mg/dL, if triglyceride levels reach >200 then itconsidered as high triglyceride levels. High triglyceride levels are a risk factor for atherosclerosis which also known as narrowing or hardening of the arteries. Research purpose: To determine the triglyceride levels of active smokers aged 30-40 years in Ujung Bulu Besar District, Bulukumba Regency. Research method: the method used is descriptive to see the description of triglyceride levels in active smokers using the ABX Pentra 400 tool. Results: 20 samples of active smokerswere taken and examined using the ABX Pentra 400 tool, then calculated to get the average value. The result of the average value of 20 samples is 211 mg/dL. Conclusion: there is an increase in triglyceride levels in active smokers at the age of 30-40 years where the average triglyceride level exceeds the normal limit >200 mg/dL.